2022
DOI: 10.1097/cu9.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Ductal prostate cancer: Clinical features and outcomes from a multicenter retrospective analysis and overview of the current literature

Abstract: ObjectiveThe aim of the study is to evaluate clinical features and outcomes after different therapeutic strategies for ductal prostate adenocarcinoma (DPC), a rare but aggressive subtype of invasive prostate cancer (PCa) accounting for, in the pure and mixed form, 1% or less and 5% or less, respectively, of all the newly diagnosed PCa.Materials and methodsPatients with a proven diagnosis of DPC undergoing surgery, radiotherapy, and androgen deprivation therapy, alone or in combination, were considered for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…[ 17 ] Because DAC often originates from the prostatic ducts around the primary urethra, most patients are found in the clinic with urinary obstruction or hematuria. [ 18 ] There is evidence that DAC has a lower PSA value at the time of diagnosis compared to APC and is therefore diagnosed at a more advanced stage. [ 19 ] Our study also confirmed this, with the majority of patients having a PSA < 10 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Because DAC often originates from the prostatic ducts around the primary urethra, most patients are found in the clinic with urinary obstruction or hematuria. [ 18 ] There is evidence that DAC has a lower PSA value at the time of diagnosis compared to APC and is therefore diagnosed at a more advanced stage. [ 19 ] Our study also confirmed this, with the majority of patients having a PSA < 10 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy plays a crucial role in the management of PCa, both with curative intent and in the salvage setting. Emerging data have placed RT as a useful therapeutic option also for oligometastatic and oligorecurrent/oligoprogressive disease (22), rare histologies (23)(24)(25), or in combination with new drugs available for hormone-sensitive and castrateresistant PCa.…”
Section: Discussionmentioning
confidence: 99%
“…DAC with other Pca subtypes is more common than pure DAC [20]. As DAC often originates from the prostatic ducts around the primary urethra, most patients are found in the clinic with urinary obstruction or haematuria [21]. There is evidence that DAC has a lower PSA value at the time of diagnosis compared to APC and is therefore diagnosed at a more advanced stage [22].…”
Section: Discussionmentioning
confidence: 99%